tìm x
a)x+2 1/6=3 1/3
b)x-2 3/7=3
c)x x 1 1/3=2 2/3
a) 4,1 + (-13,7) + 5,9 + (-6,3)
b) -5,38 . 56,25 + 5,38 . (-63,75)
2: tìm x
a) (x - 3 phần 15) : 2 phần 5 = 1 phần 3
b) 7 phần 12 + x = -5 phần 6 + -1 phần 3
c) x - 3 phần 5 . -10 phần 9 = -10 phần 3
d) 3 phần 4 + 1 phần 4 : x = -2
e) 8 : x = 2,8 - 1,2
giúp mik với!!!
2:
a: =>x-1/5=2/15
=>x=2/15+3/15=5/15=1/3
b: =>x+7/12=-5/6-2/6=-7/6
=>x=-14/12-7/12=-21/12=-7/4
c: =>x+2/3=-10/3
=>x=-4
d: =>1/4:x=-11/4
=>x=-1/4:11/4=-1/11
e: =>8:x=1,6
=>x=5
Viết theo HĐT
a) (x - 1)3
b) (2x + 3y)3
c) x3– 64.
d) 27x3+ 8y3
.
Bài 3. Tìm x, biết:
a) (x – 2)3– x2(x – 6) = 5
b) (x – 1)(x2+ x + 1) – x(x + 2)(x – 2) = 4
c) (x + 2)3– (x + 2) = 0
Bài 4. Tìm x biết (x + 2021)3+ (3x - 2022)3=(4x– 1)3
a) \(\left(x-1\right)^3\)
\(=x^3-3x^2+3x-1\)
b) \(\left(2x-3y\right)^3\)
\(=\left(2x\right)^3-3\left(2x\right)^23y+3.2x\left(3y\right)^3+\left(3y\right)^3\)
\(=8x^3-36x^2y+54xy^2-27y^3\)
Bài 3:
a: Ta có: \(\left(x-2\right)^3-x^2\left(x-6\right)=5\)
\(\Leftrightarrow x^3-6x^2+12x-8-x^3+6x^2=5\)
\(\Leftrightarrow12x=13\)
hay \(x=\dfrac{13}{12}\)
b: Ta có: \(\left(x-1\right)\left(x^2+x+1\right)-x\left(x+2\right)\left(x-2\right)=4\)
\(\Leftrightarrow x^3-1-x^3+4x=4\)
\(\Leftrightarrow4x=5\)
hay \(x=\dfrac{5}{4}\)
Câu 1:): Tìm X
A) X + 2/3 = 4/5
B) 7/9 - X = 1/3
C) X : 2/3 = 9/8
D) X x 4/7 - X x 3/4 = 10
GIẢI GIÚP MÌNH VỚI Ạ!
A) \(x-\dfrac{2}{3}=\dfrac{4}{5}\\ x=\dfrac{4}{5}+\dfrac{2}{3}\)
\(x=\dfrac{22}{15}\)
b)\(\dfrac{7}{9}-x=\dfrac{1}{3}\\ x=\dfrac{7}{9}-\dfrac{1}{3}\\ x=\dfrac{4}{9}\)
C)\(x:\dfrac{2}{3}=\dfrac{9}{8}\\ x=\dfrac{9}{8}x\dfrac{2}{3}\\ x=\dfrac{3}{4}\)
a) 3/10 x x=2/5 b) 1/8 : x - = 1/2 d) 5/6 : 3/4 1: 2/3
a) 5/6 + 3/4 1 + 2/3
b) 5/6 - 3/4 1 - 2/3
c) 5/6 x 3/4 1x 2/3
3/10 x x=2/5
x = 2/5:3/10
x = 4/3
1/8 : x = 1/2
x = 1/8:1/2
x= 1/4
5/6 : 3/4 = 5/6x4/2= 10/9
1: 2/3= 1/1 x 3/2= 3/2
5/6 + 3/4 = 19/12
1 + 2/3= 1/1+2/3= 5/3
5/6 - 3/4 = 1/12
1 - 2/3= 1/1-2/3= 1/3
5/6 x 3/4= 5/8
1/1x2/3= 2/3
a/4 =b/6 ;b/5 =c/8 vaf 5a -3b-3c
3a -5b +7c =86 vaf a+3/5 =b-2/3 =c-1/7
a-2b +c =46 vaf a/7 =b/6;b/5 =c/8
5a =8b =3c vaf a-2b +c =34
a^2 +3b^2 -2c^2 =-16 vaf a/2=b/3=c/4
(2/5 -x) :4/3 +1/2 =-4
(-3 +3/x -1/3 ) : ( 1+ 2/5 +2/3 ) =-5/4
-3x/4 .(1/x +2/7 )=0
Tìm x
a) -1/2 . x = 5
b) x-1/9 = 8/3
c) x + 5/6 = 16/42 - -8/56
d) 1 3/4x - 5 = -3 1/3
e) 3 1/3 - 3/4 : x = -1/6
g) 3/x + 5 = 15%
h) 1/2 + 1/2.3 + 1/3.4 +...+1/x(x+1) = 49/50
Tìm x
a) -1/2 . x = 5
b) x-1/9 = 8/3
c) x + 5/6 = 16/42 - -8/56
d) 1 3/4x - 5 = -3 1/3
e) 3 1/3 - 3/4 : x = -1/6
g) 3/x + 5 = 15%
h) 1/2 + 1/2.3 + 1/3.4 +...+1/x(x+1) = 49/50
a: x=5:(-1/2)=-10
b: x=8/3+1/9=25/9
c: =>x+5/6=11/21
=>x=-13/42
d: =>7/4x-5=-10/3
=>7/4x=5/3
=>x=20/21
e: =>10/3-3/4:x=-1/6
=>3/4:x=10/3+1/6=21/6=7/2
=>x=3/4:7/2=3/4*2/7=6/28=3/14
g: =>3/(x+5)=3/20
=>x+5=20
=>x=15
h: =>1-1/2+1/2-1/3+...+1/x-1/x+1=49/50
=>1-1/x+1=49/50
=>x+1=50
=>x=49
Bài 4: Tìm x
a, (x + 1)2 - x (x - 3) = 2x + 3
b, (x + 2) (x - 3 ) - (x - 3)2 = 15
c, (x + 1)3 -(x3 + 3x2 + 2x - 3) = 0
\(a,\Leftrightarrow x^2+2x+1-x^2+3x-2x=3\\ \Leftrightarrow3x=2\Leftrightarrow x=\dfrac{3}{2}\\ b,\Leftrightarrow x^2-x-6-x^2+6x-9=15\\ \Leftrightarrow5x=30\Leftrightarrow x=6\\ c,\Leftrightarrow x^3+3x^2+3x+1-x^3-3x^2-2x+3=0\\ \Leftrightarrow x=-4\)
a) \(\left(x+1\right)^2-x\left(x-3\right)=2x+3\Rightarrow x^2+2x+1-x^2+3x=2x+3\)
\(\Rightarrow3x=2\Rightarrow x=\dfrac{2}{3}\)
b) \(\left(x+2\right)\left(x-3\right)-\left(x-3\right)^2=15\Rightarrow x^2-3x+2x-6-\left(x^2-6x+9\right)=15\)
\(\Rightarrow5x=30\Rightarrow x=6\)
a) 1+4/3
b) 5/9 : 2/3
c ) 4/3-1/3x5/2
d) ( 3/2-3/8):1/2
e) 15/16 : 3/8 x 3/4
f) 7/19 x 1/3 x 7/19 x 2/3
g) 3/5x 8/27 x 25/3
h) 1/5 + 4/11 + 4/5 + 7/11
a)\(=\dfrac{3}{3}+\dfrac{4}{3}=\dfrac{7}{3}\)
b)\(=\dfrac{5}{9}\times\dfrac{3}{2}=\dfrac{15}{18}=\dfrac{5}{6}\)
d)\(=\left(\dfrac{12}{8}-\dfrac{3}{8}\right)\times2=\dfrac{9}{8}\times2=\dfrac{18}{8}=\dfrac{9}{4}\)
c)\(=\dfrac{4}{3}-\dfrac{5}{6}=\dfrac{8}{6}-\dfrac{5}{6}=\dfrac{3}{6}=\dfrac{1}{2}\)
a) 1 + 4/3 = 7/3
b) 5/9 : 2/3 = 5/6
c ) 4/3 -1/3 x 5/2
= 1 x 5/2
= 5/2
d) ( 3/2 - 3/8) : 1/2
= 9/8 : 1/2
= 9/4
e) 15/16 : 3/8 x 3/4
= 5/2 x 3/4
= 15/8
f) 7/19 x 1/3 x 7/19 x 2/3
= 7/19 x (1/3 x 2/3)
= 7/19 x 2/9
= 14/171
g) 3/5 x 8/27 x 25/3
= 3/5 x 25/3 x 8/27
= 5 x 8/27
= 40/27
h) 1/5 + 4/11 + 4/5 + 7/11
= (1/5 + 4/5) + (4/11 + 7/11)
= 1 + 1
= 2
e)\(\dfrac{15}{16}\times\dfrac{8}{3}\times\dfrac{3}{4}=\dfrac{360}{192}=\dfrac{15}{8}\)
f) \(=\dfrac{7}{19}\times\left(\dfrac{1}{3}+\dfrac{2}{3}\right)=\dfrac{7}{19}\times\dfrac{3}{3}=\dfrac{7}{19}\)
g)\(=\dfrac{600}{120}=\dfrac{600:120}{120:120}=\dfrac{5}{1}=5\)
h)\(=\left(\dfrac{1}{5}+\dfrac{4}{5}\right)+\left(\dfrac{4}{11}+\dfrac{7}{11}\right)=\dfrac{5}{5}+\dfrac{11}{11}=1+1=2\)
Bài 2: Tìm x
A) 2x+5/2=-3/5
B) 1/2:x-5/6=-2/3
C) (312-x):12,6=24,5
\(a,2x+\dfrac{5}{2}=-\dfrac{3}{5}\)
\(2x=-\dfrac{3}{5}-\dfrac{5}{2}\)
\(2x=-\dfrac{31}{10}\)
\(x=-\dfrac{31}{10}:2\)
\(x=-\dfrac{31}{20}\)
\(b,\dfrac{1}{2}:x-\dfrac{5}{6}=-\dfrac{2}{3}\)
\(\dfrac{1}{2}:x=-\dfrac{2}{3}+\dfrac{5}{6}\)
\(\dfrac{1}{2}:x=\dfrac{1}{6}\)
\(x=\dfrac{1}{2}:\dfrac{1}{6}\)
\(x=3\)
\(c,\left(312-x\right):12,6=24,5\)
\(312-x=24,5\times12,6\)
\(312-x=308,7\)
\(x=312-308,7\)
`x=3,3`
a: =>2x=-3/5-5/2=-6/10-25/10=-31/10
=>x=-31/20
b: =>1/2:x=-2/3+5/6=5/6-4/6=1/6
=>x=1/2:1/6=3
c: =>312-x=308,7
=>x=3,3